2005
DOI: 10.1051/0004-6361:20034439
|View full text |Cite
|
Sign up to set email alerts
|

Jet rotation: Launching region, angular momentum balance and magnetic properties in the bipolar outflow from RW Aur

Abstract: Abstract. Using STIS on board the HST we have obtained a spectroscopic map of the bipolar jet from RW Aur with the slit parallel to the jet axis and moved across the jet in steps of 0. 07. After applying a velocity correction due to uneven slit illumination we find signatures of rotation within the first 300 AU of the jet (1. 5 at the distance of RW Aur). Both lobes rotate in the same direction (i.e. with different helicities), with toroidal velocities in the range 5-30 km s −1 at 20 and 30 AU from the symmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
133
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(157 citation statements)
references
References 24 publications
23
133
1
Order By: Relevance
“…Jet launching regions (JLRs) are confined to the inner part of the disk with estimates from 0.01 AU for the X-wind model to a few AU for disk-wind models (e.g. 1.6 AU for RW Auriga, Woitas et al 2005). The integrated momentum loss over the launching region accelerates the center of mass of the star-disk system which coincides with the star's center for axisymmetric star-disk systems.…”
Section: Orbital Excitation By Asymmetric Jet Momentum Lossmentioning
confidence: 99%
“…Jet launching regions (JLRs) are confined to the inner part of the disk with estimates from 0.01 AU for the X-wind model to a few AU for disk-wind models (e.g. 1.6 AU for RW Auriga, Woitas et al 2005). The integrated momentum loss over the launching region accelerates the center of mass of the star-disk system which coincides with the star's center for axisymmetric star-disk systems.…”
Section: Orbital Excitation By Asymmetric Jet Momentum Lossmentioning
confidence: 99%
“…Observational details and the basic steps of the data reduction have been described in Paper I and in Woitas et al (2005). Briefly, a slit of width 0.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…In Woitas et al (2002) (hereafter Paper I) we presented reconstructed velocity channel maps of the bipolar jet in the forbidden lines, giving indications of the morphology and kinematics of the jet close to the star and at high resolution. In the second paper of the series, Woitas et al (2005), we reported signatures of rotation in both jet lobes within the first 1. 5 from the central source (about 200 AU at the distance of RW Aur).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus the distinction between tightly collimated jets and wide-angle winds informs the debate about the nature of jet launching and accretion disk physics. Since it is difficult to directly observe the wind launching regions (see Woitas et al (2005) ), the properties of large scale bipolar outflows can aid in understanding the nature of their initial conditions. In addition to questions concerning the nature of the driving winds, bipolar outflows may play an important role in modifying their natal environments.…”
Section: Introductionmentioning
confidence: 99%